N,N′-Bis(3,3-dimethylallyl)-N,N′-(propane-1,3-diyl)dibenzenesulfonamide - Khan, Islam Ullah (International Union of Crystallography, 2011)
In the title compound, C(25)H(34)N(2)O(4)S(2), the conformation of the linking N—C—C—C—N chain is gauche-anti [torsion angles = −68.49 (19) and 167.95 (14)°]. The dihedral angle between the aromatic rings is 89.64 (6)°.